Analisis Efektivitas Proses Bongkar Muat Liquefied Petroleum Gas (LPG) di PT Pertamina Energi Tanjung Sekong - Fitri, Nuril; Haryanto, Haryanto; Kartikawati, Marina; Kalmah, Kalmah (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the effectiveness of the Liquefied Petroleum Gas (LPG) loading and unloading process at PT Pertamina Energy Tanjung Sekong Terminal, a key infrastructure in Indonesia's national energy distribution. The evaluation was based on technical and operational indicators, including the Berthing Occupancy Ratio (BOR), Length Over All (LOA), berthing time, cargo volume, and vessel visit frequency. The results show that BOR ranged between 55–65%, indicating efficient jetty utilization. The average vessel LOA was 120 meters, matching the jetty’s capacity. The average berthing time was recorded at 18 hours per visit, with unloading volumes between 2,500–3,000 metric tons and vessel frequency ranging from 8 to 10 visits per month. The main constraints affecting effectiveness included extreme weather, technical equipment failures, and limited supporting facilities. This study recommends improving equipment maintenance, strengthening operational coordination, and developing a risk management system to ensure smooth and sustainable LPG handling operations at the terminal.